2014
DOI: 10.1111/jtxs.12077
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Pulsed Wave Doppler Imaging of the Esophagus Illustrates the Effects of Water Volume on Bolus Kinematics

Abstract: This study aimed to elucidate the effects of water volume on flow properties of bolus (passage time and velocities) at the esophagus orifice using ultrasonic pulsed wave Doppler method. Five healthy males and five females were asked to consume 3, 6, 9 and 12 mL water in a single swallow. An ultrasound probe was placed against each subject's neck to observe the flow properties of bolus. The velocity spectra of the bolus at the esophagus orifice were analyzed. Our results revealed that velocity of bolus was easi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(113 reference statements)
0
9
0
Order By: Relevance
“…In addition, the image signals demonstrate strong contrast that easily differentiates the tongue from its neighboring structures; therefore, ultrasonography B (bright) mode or M (motion) mode has been widely used in many studies of the tongue (Stone and Shawker 1986;Peng et al 1995Peng et al , 2000Peng et al , 2007Watkin 1998;Blissett et al 2007;Gao et al 2012Gao et al , 2013. The velocity spectrum of bolus flow in the pharynx has recently been determined by the ultrasonic pulse Doppler method (Hasegawa et al 2005;Kumagai et al 2009;Gao and Kohyama 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the image signals demonstrate strong contrast that easily differentiates the tongue from its neighboring structures; therefore, ultrasonography B (bright) mode or M (motion) mode has been widely used in many studies of the tongue (Stone and Shawker 1986;Peng et al 1995Peng et al , 2000Peng et al , 2007Watkin 1998;Blissett et al 2007;Gao et al 2012Gao et al , 2013. The velocity spectrum of bolus flow in the pharynx has recently been determined by the ultrasonic pulse Doppler method (Hasegawa et al 2005;Kumagai et al 2009;Gao and Kohyama 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The extensional viscosities of the thickened solutions were determined using the Hyperbolic Contraction Flow (HCF) system mounted on an Instron 5542 (Instron Corp., Canton, USA). The HCF method is described in detail elsewhere [ 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Water, which often causes aspiration during swallowing, travelled with a velocity of 0.5 m/s, while the velocity of yoghurt during pharyngeal transport was recorded as 0.2 m/s. Similarly, Gao and Kohyama [ 19 ] used the UVP technique to examine the influence of water volume on bolus kinematics. In that study, they concluded that reducing the volume of the water caused the passage time and the bolus velocity in the oesophagus to decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound imaging is a safe and noninvasive method that can be used to observe tongue movements during the oral processing and swallowing of soft foods (Gao et al, ; Gao & Kohyama, ). A commercially available, acoustic coupling polymer gel can also be used as an artificial tongue (Gao, Ishihara, et al, ; Gao, Nakao, Ishihara, Funami, & Kohyama, ).…”
Section: Nfri Publications In the Jtsmentioning
confidence: 99%